THE EFFECT OF SLICE THICKNESS AND FRYING TEMPERATURE CHARACTERISTICS OF PUMPKIN CHIPS BY VACUUM FRYING METHOD - Sugito Sugito; Hermanto Hermanto; Arfah Arfah (BPFP Faperta UNIB, 2013)
The objective of research was to determine the effect of slice thickness and frying temperature on the physical, chemical and sensorycharacteristics of pumpkin chips by vacuum frying method. Research used a Factorial Completely Randomized Block Design with 2 treatments and 3 replications. A factor (the slice thickness: 1, 2, and 3 mm) and B factor (frying temperature : 80, 90, and 100oC). The results showed that the slice thickness had significant effect on the crispy texture, yield, and water content of pumpkin chips. The temperature had significant effect on the lightness, chroma, crispy texture, yield, and moisture content. Interaction slice thickness and temperature had significant effect on the water content of pumpkin chips. A3B3 treatment (slice thickness 3 mm and frying temperature 100oC) was the best treatment with physical characteristic (yield 17.47%, crispy texture 183.6 gf, colour with 54.63% lightness, 42.17% chroma and 54.90o hue), chemical cha-racteristic (1.63% water content, 8.08% ash content) and sensory characteristics by scoring preferences 3.48 crispy texture, 3.2 flavour, 2 colour and 3.32 taste. A3B3 treatment had 1.58 dissoluble fiber content, 12.92 mg/mL IC50 antioxidant activity, 21.90 fat rate,1.46 ppm total carotene.